Increased Expression of Survivin in Hepatoblastoma after Chemotherapy - Uehara, Shuichiro; Oue, Takaharu; Kawatsu, Miyoko; Nara, Keigo; Fukuzawa, Masahiro (European Journal of Pediatric Surgery, 2013)
Background Survivin, an inhibitor of apoptosis, has been reported to be associated with a worse prognosis in some malignancies. However, its expression in hepatoblastoma (HB) remains to be elucidated. We assessed the survivin expression in HB specimens collected before and after chemotherapy to elucidate the impact of survivin on the outcome of HB therapy.Methods HB specimens were collected before and after 2 to 4 cycles of cisplatin-based chemotherapy from 16 patients. The survivin expression level was assessed by immunohistochemical staining and real-time polymerase chain reaction.Results Out of 16, 12 HB sections collected before chemotherapy were positive for survivin as determined by immunohistochemical staining. The intensity of survivin expression was found to significantly increase after chemotherapy. Surprisingly, all of the HB specimens obtained after chemotherapy were positive for survivin. The expression of survivin messenger ribonucleic acid from a human HB cell line, Huh-6 was significantly higher when the cells were cultured with cis-diamminedichloroplatinum(II) than when the cells were cultured without the drug.Conclusion Our results indicate that most of the primary HB tissue specimens express survivin, and its expression increased after chemotherapy, thus suggesting that survivin may concern with the survival of tumor cells, therefore be a candidate for the target of the treatment of HB.
Keywords: hepatoblastoma; surviving; chemotherapy; molecular targeted therapy